2009
DOI: 10.1159/000253847
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Doppler Parameters of the Fetal Anterior Cerebral Artery throughout Gestation

Abstract: Aim: To construct normal reference values for Doppler parameters in 2 anatomical segments of the fetal anterior cerebral artery (ACA) throughout pregnancy. Methods: The ACA was evaluated in 373 normally growing fetuses from 20 to 40 weeks of gestation. The first segment of the ACA (ACA-S1) was recorded just after its origin from the internal carotid artery in the same plane as the middle cerebral artery (MCA). The second segment (ACA-S2) was recorded distal to the outlet of the anterior communicating artery. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
2
18
0
1
Order By: Relevance
“…In this study the relative values of brain tissue perfusion increase slightly through the third trimester. These findings are consistent with those of previous studies using cerebral spectral Doppler ultrasound, which have reported decreasing impedance in the MCA and anterior cerebral artery as gestation progresses30–33. Similarly, other studies using 3D‐PDU have qualitatively assessed fetal cerebral blood perfusion and reported that brain perfusion values increase with gestational age9–12.…”
Section: Discussionsupporting
confidence: 91%
“…In this study the relative values of brain tissue perfusion increase slightly through the third trimester. These findings are consistent with those of previous studies using cerebral spectral Doppler ultrasound, which have reported decreasing impedance in the MCA and anterior cerebral artery as gestation progresses30–33. Similarly, other studies using 3D‐PDU have qualitatively assessed fetal cerebral blood perfusion and reported that brain perfusion values increase with gestational age9–12.…”
Section: Discussionsupporting
confidence: 91%
“…fetal brain circulation was examined in an axial plane at the level of circle of Willis. The ACA was then recorded in its two segments: ACA1, between its origin from the internal carotid artery and the anterior communicating artery, and ACA2, just after the anterior communicating artery [12] but before becoming the pericalloseal artery. The MCA was registered at the proximal segment after its origin from the circle of Willis.…”
Section: Methodsmentioning
confidence: 99%
“…In order to adjust for gestational age, all Doppler values were expressed in z-scores (SD values from the mean) [10,12,13,14,15,16]. Normality was considered between –1.645 z-scores (5th centile) and +1.645 z-scores (95th centile).…”
Section: Methodsmentioning
confidence: 99%
“…For the ACA, the Doppler gate was placed immediately after the origin of the ACA from the internal carotid artery. Either the MCA‐PI or the ACA‐PI values below the 5 th centile were considered indicative of cerebral blood flow redistribution and were reported as abnormal18, 21.…”
Section: Methodsmentioning
confidence: 99%